2014
DOI: 10.2174/1381612820666140317110217
|View full text |Cite
|
Sign up to set email alerts
|

Activated Immune System and Inflammation in Healthy Ageing: Relevance for Tryptophan and Neopterin Metabolism

Abstract: Immune activation not only accompanies inflammation in various disorders including infections, autoimmune syndromes and cancer, but it also represents a characteristic feature of ageing. Immune deviations which are most widely expressed in the elderly include increased neopterin production and tryptophan breakdown. These biochemical events result from the activation of the immune system and are preferentially triggered by pro-inflammatory stimuli, such as the Th1-type cytokine interferon-γ. They seem to play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 129 publications
(180 reference statements)
3
46
0
1
Order By: Relevance
“…Another inflammatory pathway by which cytokines may mediate behavioral effects is by activation of IDO [41], an enzyme expressed in multiple cell types, including macrophages, dendritic cells, microglia, astrocytes, and neurons [42]. Second, immune activation and inflammation are also accompanied by high output of reactive oxygen species and thereby may lead to the development of oxidative stress and contribute to the vitamin deficiency which is often observed in the elderly [43]. Inflammation and oxidative stress are inextricably connected in physiologic as well as disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Another inflammatory pathway by which cytokines may mediate behavioral effects is by activation of IDO [41], an enzyme expressed in multiple cell types, including macrophages, dendritic cells, microglia, astrocytes, and neurons [42]. Second, immune activation and inflammation are also accompanied by high output of reactive oxygen species and thereby may lead to the development of oxidative stress and contribute to the vitamin deficiency which is often observed in the elderly [43]. Inflammation and oxidative stress are inextricably connected in physiologic as well as disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Other special mechanism should be considered. Second, immune activation and inflammation are also accompanied by high output of reactive oxygen species and thereby may lead to the development of oxidative stress and contribute to the vitamin deficiency which is often observed in the elderly (Capuron et al, 2014). It is suggested that these changes may reflect the increase in the concentration of pro-inflammatory cytokines and other inflammatory mediators such as PG-E2 and nitric oxide whose synthesizing enzymes are also induced by these cytokines (Howren et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To further evaluate the specificity of the ratio‐based B‐vitamin markers in relation to total B‐vitamin status and not as markers of kidney dysfunction and inflammation, we calculated a combined measure of kidney dysfunction and inflammation by summing log‐transformed standardized plasma concentrations of the sensitive kidney function marker SDMA, and the inflammatory markers KTR and neopterin . The score was then used in ROC analysis by defining a dichotomous kidney dysfunction and inflammation variable using the highest 95 percentile of the score in controls as the cut‐off.…”
Section: Methodsmentioning
confidence: 99%